Pemanfaatan Ekstrak Sembung Rambat (Mikania Micrantha) Untuk Mengendalikan Gulma Babadotan (Ageratum Conyzoides L.) - Tiara Lestari; Wina Arisah Sipahutar; Silvia Rusmaini Sipahutar; Aura Anantasya Putri; Diaz Alfharibi Damanik; Guntoro Guntoro (Universitas Khairun, 2026)
Reliance on synthetic chemical herbicides in the agricultural sector has triggered environmental degradation and weed resistance, necessitating eco-friendly bioherbicide alternatives. This study aims to evaluate the phytotoxic efficacy of sembung rambat (Mikania micrantha) extract in controlling babadotan (Ageratum conyzoides L.) weed. The method employed was a Systematic Literature Review (SLR) adhering to the PRISMA protocol, utilizing Publish or Perish software to screen articles from Google Scholar, Sinta, and Scopus databases published between 2022 and 2026. The synthesized data reveals that Mikania micrantha leaf extract macerated with 96% ethanol contains secondary metabolites rich in phenols, flavonoids, and saponins that effectively suppress target weed growth. An optimal concentration of 40% inhibits weed seed germination by up to 98.65% in the pre-emergence phase and induces vegetative mortality up to 94.35% in the post-emergence phase. This biological suppression operates systemically through the disruption of cell membrane permeability and the inhibition of the chloroplast electron transport chain, leading to total necrosis. This study concludes that Mikania micrantha holds significant potential as a commercial bioherbicide to support sustainable agriculture.